Macronutrients and dissolved iron in a land-ocean approach: Influences of contamination by ore tailings in Southeastern Brazil - Cagnin, Renata Caiado; Longhini, Cybelle Menolli; Costa, Eduardo Schettini; da Silva, Cesar Alexandro; Zorzal-Almeida, Stéfano; Mendes, Danniel; Pasa, Vânya Márcia Duarte; Barbeira, Paulo Jorge Sanches; Delazari-Barroso, Alessandra; Gücker, Björn; Boëchat, Iola Gonçalves; Lima, Ana Teresa; et al. (Frontiers in Marine Science, 2022)
Recently, many dam rupture disasters related to the mining industry have caused significant disruption to ecosystems globally. Contaminants, including nutrients in excess, can be transported from the river watersheds to the ocean in great quantities. In 2015, millions of m3 of iron ore tailings were released in the Doce River in southeastern Brazil, leading to several damaging effects to the river and marine ecosystem. So far, few studies have integrated the impact of these tailings on the river and the sea simultaneously. This research aims to provide a perspective on the macronutrients and iron concentrations and balance in the Doce River and the adjacent continental shelf, the related abiotic factors and the phytoplankton response under a new steady state of iron enrichment environment. The iron ore tailings increased the concentrations of nutrients in the river and on the continental shelf, especially for dissolved silica and iron. There was also a long-term indirect phosphorus enrichment associated to adsorption/desorption onto Fe-oxides and a nitrogen increase possibly due to N-fixing enhanced by iron. N fixation/remineralization predominates in the river watershed, while in the sea, the hydrodynamics provides nutrients supplied by the river and recycling from sediment resuspension. Nutrient ratios show DIP limitation in the river, while the complex marine environment brings both limitations on DIN, DIP, and DSi, as well as a stoichiometric equilibrium to the dataset. The phytoplankton response to the abiotic factors was more representative in the river watershed than on the continental shelf. This work emphasizes the importance of reporting local data for understanding global land-ocean nutrient fluxes and their potential influence on primary productivity and trophic chain balance.